Analisis Sentimen Ulasan Google Review New Star Cineplex Pasuruan menggunakan Artificial Neural Network (ANN) - Sandrian Yulian Firmansyah Noorihsan; Nanang Yudi Setiawan; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Service provider companies must be able to satisfy the expectations of their customers. Therefore every company must find a way to satisfy its customers. After the company knows the factors that cause consumer dissatisfaction, the next step is to make changes to the cinema. One of the things that can be done to encourage the film industry in Indonesia is to improve the quality of cinemas in Indonesia by means of sentiment analysis of customer reviews as material for evaluating cinema quality analysis. According to New Star Cineplex Pasuruan, customer reviews are key for quality analysis. The classification method that will be used to carry out sentiment analysis of 796 customer reviews of New Star Cineplex Pasuruan which have gone through the text preprocessing stage is an Artificial Neural Network (ANN) at the level of price, place and customer service aspects. Evaluation of the ANN model using the fusion matrix shows that the value of the model accuracy has a proportion of 88%. On positive sentiment, it has a precision of 86%, 90% recall, 88% f1-score. Negative sentiment has a precision value of 89%, 84% recall, 86% f1-score. The results of the root cause analysis are evaluation recommendations in the form of gradual improvements to the general aspect of facilities, increased notifications and provision of queue numbers on aspects of customer service, and improvement of facilities on the price aspect.